MOTIVASI DAN RETENSI SUMBER DAYA MANUSIA KESEHATAN DI DAERAH TERPENCIL DI INDONESIA - Pasaribu, Karl Frizts; Panjaitan, Jenita Oktavia; Akita, Amalia; Girsang, Deddy Ray (UNIKA Santo Thomas, 2025)
The availability of healthcare workers in remote areas is a major challenge within the healthcare system in Indonesia. This study aims to analyze the motivation factors and retention strategies of healthcare workers in remote regions through a systematic literature review method. A total of 21 relevant scientific articles were analyzed to understand the factors influencing the motivation and retention of healthcare workers. The study results show that healthcare workers' motivation is influenced by financial incentives, career development, as well as social and work environment factors. Policies such as the Nusantara Sehat Program and special capitation have helped improve the distribution of healthcare workers, although there are still challenges in their implementation. Non-financial factors, such as job satisfaction and support, also play a role in the sustainability of healthcare workers in remote areas. Therefore, more comprehensive policies are needed to ensure the sustainability of programs and the equitable distribution of healthcare workers across Indonesia.